ANALYSIS FACTORS OF PSYCHOSOCIAL STRESS IN PREGNANCY - Elizabet Catherine Jusuf (Nusantara Medical Science Journal, 2018)
The Pregnancy period begins from conception until birth. It is hard to figure out if the pregnancy will get any problem. The process will involve emotional, physical and social alteration in the family. Until now,the maternal emotional condition, psychosocial stress are rarely to watch over by medical practisioners meanwhile at some study said that maternal psychosocial stress influence the outcome of baby. The aim of this study to analyze some factors that is associated to psychosocial stress in pregnancy women. This was a cross-sectional study of collected by using questionaires, were comprised of 11 questions using likert-scales, then using bivariat analysis by t-test and chi square to evaluate the sample characteristic at teaching hospital Hasanuddin University in 2015. There are 158 pregnant woman,  shows who are in the age of 26,25 ± 6,319, suffer from stress, who are in their gestasional age of 30,63 ± 9,164 weeks will be going through the high level of stress. The age of pregnant women and their gestasional age in this study do not influence significantly toward psychosocial stress. Social economic factors such as level of education, occupation, and parity influence the pregnant women psychosocial stress level.